2007
DOI: 10.1128/mmbr.00001-07
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Physiology of ABC-Type Transporters Contributing to Multidrug Resistance in Bacteria

Abstract: SUMMARY Membrane proteins responsible for the active efflux of structurally and functionally unrelated drugs were first characterized in higher eukaryotes. To date, a vast number of transporters contributing to multidrug resistance (MDR transporters) have been reported for a large variety of organisms. Predictions about the functions of genes in the growing number of sequenced genomes indicate that MDR transporters are ubiquitous in nature. The majority of described MDR transporters in bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
202
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(213 citation statements)
references
References 146 publications
(187 reference statements)
4
202
1
6
Order By: Relevance
“…In addition to the 23S rRNA, few mutations were common to at least two independent mutants. ABC proteins are involved in multidrug resistance in several microbial eukaryotic pathogens (Ouellette and Légaré 2002), but also in bacteria (Lubelski et al 2007), and mutations within putative promoter regions of operons coding for ABC proteins were observed in more than one mutant (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the 23S rRNA, few mutations were common to at least two independent mutants. ABC proteins are involved in multidrug resistance in several microbial eukaryotic pathogens (Ouellette and Légaré 2002), but also in bacteria (Lubelski et al 2007), and mutations within putative promoter regions of operons coding for ABC proteins were observed in more than one mutant (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Our gene disruption experiments of resistant cells provided evidence that PatA and PatB are associated with resistance to linezolid, although their role seems to be minor (Table 3). It has been suggested that they form heterodimers (Lubelski et al 2007), and inactivation of both genes in the same cell may lead to further resistance. In addition to their role in linezolid resistance, analysis of the phenotype of either patA or patB disruptants clearly implicate the two ABC proteins in a multidrug resistance phenotype due to increased RNA expression ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…약물 유출을 담당하는 펌프는 항생제의 종류에 구 애 받지 않고 다양한 항생제, 살균 소독제 및 각종 독성 물질들도 동시에 유출시키며 특이성이 크지 않기 때문에 한번도 노출된 적이 없는 서로 다른 계열의 항생제도 유출할 수 있어 동시에 여 러 항생제에 내성을 나타내도록 한다 (Levy, 1992;Saier et al, 1994). 세균에서 알려진 다중약물 유출 펌프는 에너지원과 염기 서열의 유사성에 따라 크게 다섯가지로 구분할 수 있다: 1) ATP binding cassette (ABC) superfamily (Lubelski et al, 2007), 2) 장알균속 세균의 다중약물 유출 펌프 127 major facilitator superfamily (MFS) (Pao et al, 1998), 3) small multidrug resistance (SMR) superfamily (Jack et al, 2001), 4) multidrug and toxic compound extrusion (MATE) superfamily (Kuroda and Tsuchiya, 2009), 5) resistance-nodulation-cell division (RND) superfamily (Tseng et al, 1999;Seeger et al, 2008). 이중 그람양성 세균은 ABC, MFS 및 SMR 타입의 유출 펌프를 갖고 있는 것으로 보고되었다 (Depardieu et al, 2007).…”
unclassified
“…Untuk mencapai optimasi pemberian antibiotic profilaksis, terdapat beberapa hal yang menjadi pertimbangan pada pemberiannya, yaitu: apakah terapi profilaksis diperlukan, apa jenis antibiotik yang akan diberikan, apakah antibiotic diberikan secara oral atau intravena, kapan memulai terapi dan berapa lama diberikan. 1,2,3 Infeksi daerah pembedahan merupakan salah satu masalah dalam penanganan pasca bedah. Insidensnya menduduki peringkat kedua sebagai penyebab infeksi nosokomial, dan berdampak pada peningkatan morbiditas dan mortalitas, dan biaya pengobatan.…”
unclassified